Bermain Sambil Belajar: Upaya Peningkatan Calistung pada Anak Yatim dan Putus Sekolah di Desa Ampung Julu - Farid, Ahmad Salman (Universitas Gajah Putih, Indonesia, 2023)
This activity was carried out in response to the challenge of low literacy rates among orphaned and school drop-out children in the village of Ampung Julu, Batang Natal District, Mandailing Natal Regency. The evaluation results indicate a significant improvement in the reading, writing, and arithmetic skills of children, confirming that educational games can be an effective method in shaping academic skills. The program also instilled high intrinsic motivation among the children, perceiving learning as an enjoyable experience. In addition to the positive impact on academic aspects, educational games also foster social and emotional skills in children, creating a crucial foundation for holistic personal development. The success of the program relies not only on the contributions of the students but also actively involves the participation of the local community, including parents and village authorities. This close collaboration creates sustainable support and enhances the positive impact of the program. These outcomes not only bring about changes in the education of children but also alter the community's perception of the significance of education as a tool for creating positive changes in their lives. The success of the